2014
DOI: 10.1681/asn.2014020174
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin Antagonists in Diabetic Nephropathy

Abstract: The pivotal discovery of endothelin (ET) by Yanagisawa and colleagues 1 in 1988 generated wide interest in this peptide, as evidenced by the nearly 27,000 articles published to date that have examined its role in biology. ET is now recognized as essential to the function of various organs and metabolic processes. 2 The ET family consists of three 21-amino acid peptides-ET-1 (ubiquitous and most biologically active), ET-2, and ET-3-that exert their actions via two receptor subtypes: ET A and ET B 2 . Activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
(25 reference statements)
1
11
0
Order By: Relevance
“…There is ongoing research attempting to improve the risk-benefit ratio for therapeutic agents targeting the endothelin pathway to delay kidney disease progression. 26 Our study findings add to the substantial mechanistic evidence from basic science research and clinical trials on the endothelin pathway and kidney disease.…”
Section: Discussionsupporting
confidence: 52%
“…There is ongoing research attempting to improve the risk-benefit ratio for therapeutic agents targeting the endothelin pathway to delay kidney disease progression. 26 Our study findings add to the substantial mechanistic evidence from basic science research and clinical trials on the endothelin pathway and kidney disease.…”
Section: Discussionsupporting
confidence: 52%
“…This deletion resulted in less albuminuria and protection from glomerulosclerosis and podocyte loss ( Lenoir et al, 2014 ). These results suggest that in mice at least, the ET B receptor may play as important a role as does the ET A receptor in diabetes, whereas previous studies have suggested the latter was the main subtype mediation the deleterious actions of ET-1 ( Chandrashekar and Juncos, 2014 ).…”
Section: Phenotypes Of Cell-specific Genetic Modifications In Thementioning
confidence: 59%
“…ACE inhibitors also reduce endothelial activation by increasing NO production independently of their anti-hypertensive effects (76). Podocytes lacking both endothelin receptors are protected from damage in animal models of diabetes and an endothelin antagonist reduced proteinuria in patients with diabetic nephropathy (156). Targeting of VEGF-A (157) or PDGF has proved more challenging because the relationships between angiogenesis, inflammation and fibrosis are still not fully understood.…”
Section: Implications For Treatmentmentioning
confidence: 99%